Kepastian Hukum Putusan Arbitrase Dalam Penyelesaian Sengketa Komersial Di Indonesia (Studi Kasus Putusan Mahkamah Agung Periode 2015-2023) - Enjelita Berliana; Rehan Rehan; Akhmad fajri; Puput Putriani; Melysa diah lestari; Holijah Holijah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Legal Certainty of Arbitration Awards in Commercial Dispute Resolution in Indonesia is a crucial issue amid rapid economic growth, with investment realization reaching IDR 1,186 trillion in 2022. This study aims to analyze the regulation, practice, and obstacles to the legal certainty of arbitration awards under Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution (Arbitration Law). Employing a normative juridical approach with statutory, conceptual, and case study analysis of Supreme Court decisions from 2015-2023, the research finds that although the Arbitration Law adopts the UNCITRAL Model Law and limits annulment grounds (Article 70), court practices often involve judicial overreach through expansive public policy interpretations, resulting in 28% of annulment petitions being granted. Key obstacles include inconsistent jurisprudence and lack of harmonization with the 1958 New York Convention. Compared to Singapore, Indonesia lags in minimizing judicial intervention. The conclusion states that legal certainty of arbitration awards is suboptimal, necessitating amendments to the Arbitration Law to strengthen finality and restrict annulment grounds. Recommendations include establishing a public policy expert panel and judicial training. This study contributes to enhancing Indonesia's investment climate.